Estimation of Yield Loss Due to Striped Disease in Peanut Plants in Palopo City, South Sulawesi - Kasim, Niken Nur; Prihatin, Prihatin; Sukmawati, Sri; Wiridannisaa, Nurul (Jurnal Biologi Tropis, 2024)
Palopo City is one of the peanut production centres in South Sulawesi. However, from 2008 to 2020, groundnut production in Palopo City has decreased. Recently, in South Sulawesi, it was reported that peanut stripe virus infection has spread widely and evenly in peanut plants. Symptoms of stripe disease include dark green and light green leaf colour, chlorosis, and can cause stunting. This study aims to determine the estimation of yield loss caused by stripe disease in peanut plants in Polopo City, South Sulawesi. This research was conducted in a farmer-owned groundnut field located in Purangi Village, Sendana Subdistrict, Palopo City, South Sulawesi, from January to May 2023. Parameters observed were plant height, disease severity and incidence, and yield loss. Observations were made 6 times on plants aged 4 to 9 weeks after planting. The results showed that the symptoms of striped disease showed that the growth of peanut plant height was inhibited, and caused a decrease in the number of pods, pod weight, and pod number. Disease severity increased to 57.2% and disease incidence to 46.6%. Yield loss caused by stripe symptoms in peanut plants was 43.78%, indicating that high disease severity and incidence can reduce yield.